Role of NFE2L1 in the Regulation of Proteostasis: Implications for Aging and Neurodegenerative Diseases - Aswathy Chandran; Haley Jane Oliver; Jean-Christophe Rochet (Biology, 2023)
A hallmark of aging and neurodegenerative diseases is a disruption of proteome homeostasis (“proteostasis”) that is caused to a considerable extent by a decrease in the efficiency of protein degradation systems. The ubiquitin proteasome system (UPS) is the major cellular pathway involved in the clearance of small, short-lived proteins, including amyloidogenic proteins that form aggregates in neurodegenerative diseases. Age-dependent decreases in proteasome subunit expression coupled with the inhibition of proteasome function by aggregated UPS substrates result in a feedforward loop that accelerates disease progression. Nuclear factor erythroid 2- like 1 (NFE2L1) is a transcription factor primarily responsible for the proteasome inhibitor-induced “bounce-back effect” regulating the expression of proteasome subunits. NFE2L1 is localized to the endoplasmic reticulum (ER), where it is rapidly degraded under basal conditions by the ER-associated degradation (ERAD) pathway. Under conditions leading to proteasome impairment, NFE2L1 is cleaved and transported to the nucleus, where it binds to antioxidant response elements (AREs) in the promoter region of proteasome subunit genes, thereby stimulating their transcription. In this review, we summarize the role of UPS impairment in aging and neurodegenerative disease etiology and consider the potential benefit of enhancing NFE2L1 function as a strategy to upregulate proteasome function and alleviate pathology in neurodegenerative diseases.